PHYSICAL ACTIVITY AND EDUCATION IN THE ELDERLY HEALTH: A REPORT ON AN EXPERIENCE PROMOTED BY NURSING STUDENTS (Fiep Bulletin - online, 2011)
The present report is an experience with the goal to demonstrate preventive action based on building healthy habits. The project was conducted by nursing students as an extra extension project. This extension project started on July 2010 and its being developed by 8 (eight) undergraduate students under the coordination of 2 (two) professors from Rio Grande do Norte State University (UERN). The project has a partnership with the Municipal Health Department, Family Health Program (PSF) and the community from the DNER neighborhood in the Santa Cruz (RN) municipality. Weekly walks with the elderly group are promoted on Tuesdays at the end of the afternoon Additionally, 2 or 3 hour long by weekly thematic workshops at the Basic Health Unit (UBS) with a group or 15 elderly individuals are being performed. The activities boosted interpersonal relationships among the elderly in the neighborhood as well as with the family Health Team and the academic community. Furthermore the project impacted positively on the elderly self determination and self esteem within the Santa Cruz community it self. It's noteworthy to mention the strengthening of the role played by the University regarding the contextual challenges lived by the elderly population. Thus it's also important to notice that the strengthening of partnerships among the academic community, the management of health services and the elderly population may give birth to opportunities of learning experience to all parts involved and the possibility to exercise a more humane citizenship.
Keywords: Elderly; Physical Activity; Health promotion